Alteraciones de la salud mental y aborto espontáneo en mujeres. - Almache Remache, Marilyn Gisell (2025)
Spontaneous abortion is the involuntary termination of pregnancy before the twentieth week of gestation. It happens when the embryo or fetus cannot continue developing, and consequently, the body expels the gestational tissue. The purpose of this research was to analyse the impact on women's mental health after a spontaneous abortion through bibliographic research at a descriptive level. A bibliographic review of different scientific articles, within the last ten years, was carried out in other languages, like English, Spanish, and Portuguese, by collecting publications in scientific databases such as PubMed Central, Dialnet, Google Scholar, Scielo, Scopus, Web of Science, Redalyc, Elsevier, and ProQuest, allowing a total of 28 articles to be compiled under different rent quality criteria to achieve review processing under the CRF-QS matrix methodology. This contains an article evaluation including 19 items. The results demonstrate the risk factors in women with a history of spontaneous abortion, anxiety, depression, and post-traumatic stress disorder (PTSD). This is how we can see it in the different studies, as the pathologies of higher percentages, however, some in a lower proportion, such as substance consumption (alcohol, marijuana), bipolar disorder, and obsessive-compulsive disorder. Therefore, spontaneous abortion can represent a critical point in the homeostasis of a woman's life, which leads to a significant emotional alteration. An empathic and holistic approach is necessary for society to consider that this problem can have consequences, both physical and psychological.